Rehabilitation and Reintegration Programming Following Female Genital Fistula Surgery: A Scoping Review - El Ayadi, Alison M (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To examine the range of rehabilitation and reintegration services provided as adjunct to genital fistula surgery, map the existing programming and outcomes, and identify areas where additional research is necessary. Methods: Our scoping review is informed by existing methodological frameworks and conducted in accordance with PRISMA guidelines.The search strategy was designed in collaboration with a medical librarian and is applied to nine biomedical, public health, and social science databases. Grey literature is identified through targeted searches and relevant organizational websites. Two primary reviewers independently screened titles and abstracts of all articles, followed by full-text screening and standardized data extraction. Eligible articles will discuss research or programmatic efforts around service provision in adjunct to surgery. Results: The literature review is currently underway and preliminary results including summary tables and narrative will be available to share at the ISOFS conference. Conclusions: The results of this scoping review will help in understanding and describing what is known and unknown about rehabilitation and social reintegration of women following genital fistula surgery in sub-Saharan Africa and may be useful in developing and evaluating social reintegration projects.